Evaluasi Efektifitas Jaringan Pos Hujan dalam Mitigasi Kebencanaan di Provinsi Bengkulu - Nisa, Ania Maulidiah; Darmawan, Yahya (Universitas Budi Luhur, 2024)
This study aims to evaluate the rain post network using the Kagan-Rodda method in Bengkulu Province, especially for supporting the disaster mitigation of hydro-meteorology. In order to obtain an accurate and efficient number and location point of the rain post network, it is necessary to evaluate the existence of existing rain posts. The method used in this research is descriptive quantitative where calculations are made on the method of analyzing the rain post network evaluation based on WMO standards and based on the Kagan-Rodda method analysis. The results of the research on the WMO standard evaluation analysis of the rain post network show that 52 rain posts are included in the minimum density category, 22 rain posts are classified as maximum density, and 42 others have normal density. Based on the analysis of the Kagan-Rodda method, several smoothing errors were obtained, namely 1%, 2%, 3%, 4%, and 5%. With the value of the number of rain posts that are still lacking in the selected smoothing error recommendations, rain posts can be procured, so that accurate and ideal rainfall analysis results will be obtained.